PERANCANGAN WEBSITE COMPANY PROFILE FARM KOI GURAME MENGGUNAKAN PLATFORM WIX - Mohammad Imam Shalahudin; Hari Setiyani; Jefri Rahmadian; II Widya (JRIS : Jurnal Rekayasa Informasi Swadharma, 2026)
The development of information technology offers significant opportunities for businesses to use digital media for promotion and communication. Farm Koi Gurame is a business specializing in koi and gourami cultivation, and it requires modern promotional media to reach a wider market. This study aims to design a company profile website using the Wix platform as a practical, efficient solution that does not require programming skills. The method used in this study is the Multimedia development life cycle (MDLC), which consists of six stages: concept, design, material collection, assembly, testing, and distribution. The result of this study is an interactive website that provides comprehensive information on the business profile, product gallery, customer testimonials, and contact features, all easily accessible across various devices. The website features an attractive design, easy-to-understand navigation, and a responsive design for optimal use across various platforms. Testing was conducted through direct user trials, demonstrating that the website can enhance the business’s professional image and facilitate the dissemination of information to potential customers. The results of the study indicate that using the Wix platform with the MDLC method can be an effective and efficient solution for the digitalization of small businesses, especially for increasing promotion, branding, and market reach through online media professionally and reliably.Perkembangan teknologi informasi memberikan peluang besar bagi pelaku usaha untuk memanfaatkan media digital sebagai sarana promosi dan komunikasi. Farm Koi Gurame merupakan usaha di bidang budidaya ikan koi dan gurame yang membutuhkan media promosi modern untuk menjangkau pasar yang lebih luas. Penelitian ini bertujuan untuk merancang website company profile dengan memanfaatkan platform Wix sebagai solusi praktis dan efisien tanpa memerlukan keahlian pemrograman. Metode yang digunakan dalam penelitian ini adalah Multimedia development life cycle (MDLC), yang terdiri dari enam tahapan: concept, design, material collecting, assembly, testing, dan distribution. Hasil dari penelitian ini adalah sebuah website interaktif yang menyajikan informasi lengkap tentang profil usaha, galeri produk, testimoni pelanggan, serta fitur kontak yang mudah diakses melalui berbagai perangkat. Website dirancang dengan tampilan menarik, navigasi yang mudah dipahami, serta desain yang responsif agar dapat digunakan secara optimal di berbagai platform. Pengujian dilakukan melalui uji coba langsung kepada pengguna, dan menunjukkan bahwa website mampu meningkatkan citra profesional usaha serta mempermudah penyebaran informasi kepada calon pelanggan. Hasil penelitian menunjukkan bahwa penggunaan platform Wix dengan metode MDLC dapat menjadi solusi efektif dan efisien dalam proses digitalisasi usaha kecil, terutama dalam meningkatkan promosi, branding, dan jangkauan pasar melalui media online secara profesional dan terpercaya.